POLYMORPHISM OF INTERLEUKIN-10 (-819) GENE IS NOT ASSOCIATED WITH LIVER DAMAGE AMONG CHRONIC HEPATITIS B PATIENTS - Ramadhani, Nur'aina ID; Arfianti, Arfianti (JOURNAL OF WIDYA MEDIKA JUNIOR, 2021)
Introduction: Chronic hepatitis B (CHB) is characterized by chronic liver inflammation andhepatocellular damage caused by hepatitis B virus (HBV), leading to fatal liver diseases such as cirrhosis and hepatocellular carcinoma (HCC). Liver damage causes elevated levels of serum alanine aminotransferase (ALT). Previous studies have shown that IL-10 gene polymorphism (-819 C/T) is linked to several diseases, including inflammatory, autoimmune diseases, and cancer. Purpose: To investigate the relationship between IL-10 gene polymorphisms (-819 C/T) and liver damages in chronic hepatitis B patients at Arifin Achmad Regional Hospital, RiauProvince.Method: This study was an analytical study with a cross-sectional approach. Liver damages were examined by measuring ALT levels, and IL-10 gene polymorphisms were analyzed using Amplification-Refractory Mutation System Polymerase Chain Reaction (ARMS-PCR). Results: There were 74 subjects included in this study, aged 45.47±13.42 years old,consisting of 43 males (58.1%) and 31 females (41.9%). Of 74 subjects, 35 CHB patientswere presented without complication, 26 CHB patients were complicated with cirrhosis, and 13 CHB patients were complicated with hepatoma. The genotype of the IL-10 (-819) gene polymorphism in this study was found as follows: CT genotype in 34 subjects (45.9%), TT genotype in 30 subjects (40.5%), and CC genotype in 10 subjects (13.5%). There was nosignificant relationship between IL-10 gene polymorphisms (- 819) and liver damage inchronic hepatitis B patients (p> 0.05).Conclusion: IL-10 gene polymorphism (-819) may not contribute to liver damages amongCHB patients.